Biodiversidade da fauna subterrânea na área cárstica de São Domingos, nordeste de Goiás: relevância versus visibilidade de táxons - Simões, Luiza Bertelli (2013)
In this issue, we did a survey of subterranean fauna in a karstic area from northeast of Goiás, considering both the tiny aquatic invertebrates as representatives of terrestrial communities. We verify the species composition in 13 caves belonging to the regions of São Domingos and Posse. Part of the region of São Domingos includes a large conservation area, with about 50.000 ha, the Terra Ronca State Park (PETER), where there are large number of caves well known to science and intense tourist activity, which threatens the integrity of these fragile systems. In contrast, the caves of the region of Posse are less visited and almost unknown when it comes to its biology. For publication purposes, we divide our work in three chapters. The first one features the terrestrial invertebrate fauna in these underground environments. We verified the richness, diversity, taxonomic distinctness and faunal similarities between caves sampled in both regions. Moreover, we highlight the records of new, rare and/or troglobitic species. We guaranteed accurate access to this fauna through six occasions collections systematized in different seasons over the years of 2010, 2011 and 2012. We sampled differently these cavities by sampling efforts that ranged from one to three replicates, except for Angélica Cave. The latter was sampled at six times in order to investigate variance in fauna according to different periods of collecting and some environmental factors. Thus, in the second chapter, we aim to verify the influence of seasonality, zoning, availability and complexity of substrates in the faunal composition of this cave. Moreover, in these first two chapters, we discussed the importance of sampling by combined methods, proposing the use of the method of squares plus the usual collecting by active search. As the terrestrial hypogean fauna is more visible, it has been studied in more detail in Brazil. Rather, the diversity of tiny aquatic organisms is clearly underestimated, both for its lower visibility as the lack of adequacy of sampling methods for collecting these animals. However, most of the underground systems in this and other Brazilian karstic areas have large karst drainage systems, with diverse passages for water infiltration in the subterranean environment, such as the capture of superficial rivers and rainwater. The percolating water produces extensive network of potential micro-habitats, from small fissures filled with air and/or water to temporary or permanent pockets, which is an unsaturated zone known as epikarst. Aware of the necessity to study this unique subterranean horizon, in the third chapter, we analyze the richness of aquatic microorganisms present in some caves in this area. Using plankton nets, we filtered water in all potential aquatic habitats as drips, travertine (pockets of water), epikarstic and groundwater rivers, as well as areas of resurgence and epigean rivers surrounding some of the caves. We observed the degree of faunal similarity between different environments sampled. Finally, some physical and chemical variables of water were measured in order to find taxa-environment relationships.